Severe congenital factor XIII deficiency caused by novel W187X and G273V mutations in the F13A gene; diagnosis and classification according to the ISTH/SSC guidelines. (29th November 2013) - Souri, M.; Biswas, A.; Misawa, M.; Omura, H.; Ichinose, A.
Summary: Factor XIII (FXIII) consists of the A and B subunits (FXIII‐A and FXIII‐B) and stabilizes fibrin clots. Defects in either the FXIII‐A or FXIII‐B gene lead to congenital FXIII deficiency, which manifests a life‐long haemorrhagic tendency. Thus, prophylactic FXIII replacement therapy is recommended. To establish a management plan for a 30‐year‐old male patient with 'indefinite' FXIII deficiency (<40% of the normal FXIII), he was characterized by state‐of‐the‐art techniques as guided by the FXIII/Fibrinogen subcommittee of ISTH/SSC. FXIII activity turned out to be virtually undetectable by three functional assays. Four immunological assays detected essentially no FXIII protein, FXIII‐A antigen, and A2 B2 antigen, but normal FXIII‐B antigen. Accordingly, he was diagnosed as a 'severe' FXIII‐A deficiency case. He had no anti‐FXIII antibodies, because a 1:1 cross‐mixing test (ammonia release assay) and a five‐step mixing test (amine incorporation assay) between his plasma and normal plasma demonstrated deficiency patterns. Furthermore, a dosing test using plasma‐derived FXIII concentrates revealed its normal recovery. DNA sequencing analysis identified two novel mutations, W187X & G273V, in the F13A gene. Genetic analyses confirmed that he was a compound heterozygote and his mother and sister were heterozygotes of either one of these mutations, indicating the hereditary nature of this disorder. Molecular modelling predicted that the G273V mutation would cause clashes with the surrounding residues in the core domain of FXIII‐A, and ultimately would result in the instability of the mutant molecule. Detailed characterization of 'indefinite' FXIII deficiency made it possible to make its definite diagnosis and best management plan.